Evaluasi Sistem Drainase Menggunakan Storm Water Management Model (SWMM) dalam Mencegah Genangan Air di Kota Tarakan - Rahmat Faizal; Noerman Adi Prasetya; Zikri Alstony; Aditya Rahman (Borneo Engineering : Jurnal Teknik Sipil, 2019)
Tarakan City experiences problems with standing water during the rainy season, especially in the west Tarakan sub-district which is the center of Tarakan. This puddle not only submerged settlements and offices but also shops and access roads that caused considerable economic losses. An evaluation was carried out by using the Storm Water Management Model (SWMM). SWMM is a rainfall-runoff simulation model used for simulating the quantity and quality of surface runoff from urban areas. Based on the evaluation using SWMM software, the drainage system in Tarakan, especially in Jalan Mulwarman has several inundated channels, namely channels 2, 3, 4, 5, 6, 7, 11, 12, 13, 14. This is influenced by the dimensions of the drainage channel that cannot accommodate existing water runoff and sediment thickness that covers the drainage channels so that the capacity is reduced, if it rains it will cause puddles at several points in Tarakan City. In order to deal with these puddles, it is necessary to change the dimensions of the channel and routinely dredge sediments that cover the drainage channels.